172,875 views
42 votes
42 votes
Help and explain ///////////////////////////

Help and explain ///////////////////////////-example-1
User OlivierTerrien
by
2.9k points

1 Answer

9 votes
9 votes

Hello,

First, you must understand that

(f-g)(x) means f(x)-g(x) it is the difference of two functions :

f(x)=2x+4 and g(x)=3x-7

f(5)=2*5+4=10+4=14

g(5)=3*5-7=15-7=8

So, (f-g)(5)= f(5)-g(5)=14-8=6

Answer A: none of the choices are correct.

An other way to do it:

(f-g)(x)=f(x)-g(x)=2x+4-(3x-7)= 2x-3x+4+7=-x+11

if x= 5 then (f-g)(5)=-5+11=6

User Cengiz
by
2.2k points